A Wedding at the Orange Blossom Inn - Gray, Shelley Shepard (New York, NY, 2015)
"Emma, a widow with three daughters, and Jay, a widower with three sons, understand each other's struggles. When Jay's oldest son becomes engaged, Emma helps with the wedding preparations. Jay want to court Emma in earnest, but Emma's relatives are troubled by the prospect of her moving on"--
Keywords: Fiction; Dating (Social customs); Fiction; Man-woman relationships; Fiction; Widowers; Widows; Fiction; Single parents; Fiction; Amish; Fiction; Romance fiction; Christian fiction